2013
DOI: 10.4018/jcit.2013100104
|View full text |Cite
|
Sign up to set email alerts
|

Using Electronic Health Records and Data Warehouse Collaboratively in Community Health Centers

Abstract: The organization Community Partners HealthNet (CPH), Inc. is a so-called Health-Center-Controlled Networks (HCCNs) that provide health information technologies, in particular Electronic Health Records and Data Warehouse, to participating community health centers (CHC) and rural health clinics (RHC). All 16 member organizations (CHCs and RHCs) in CPH are non-profit health care organizations providing primary health care to individuals in medically underserved areas. To provide quality and accessible health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…139,140 It has also been suggested that interoperable networks might lead to the redesign of professionals' working practices, which in turn could produce better patient outcomes. 141 There might, then, be system-wide improvements in patient safety that are attributable to a network as a whole rather than to the actions of single teams of professionals, discussed in the last six chapters. Equally, health and social care may face high transaction costs, partly due to information asymmetries (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…139,140 It has also been suggested that interoperable networks might lead to the redesign of professionals' working practices, which in turn could produce better patient outcomes. 141 There might, then, be system-wide improvements in patient safety that are attributable to a network as a whole rather than to the actions of single teams of professionals, discussed in the last six chapters. Equally, health and social care may face high transaction costs, partly due to information asymmetries (e.g.…”
Section: Introductionmentioning
confidence: 99%